Kognition und Reflexion: Zur Theorie filmischen Denkens - Kappelhoff, Hermann (Cinepoetics, 2018)
The discourse of sound motion pictures has evolved to become a cultural practice through which people attempt to grasp their subjective cognitive reality as part of a shared world. By developing a poetological theory of filmic thinking and the "cinematic metaphor," this study shows how filmic images generate an understanding and thinking that introduces new differences and modalities into this shared reality.